Mediating role of psychological distress on the relationship between fear of COVID-19 and burnout among healthcare providers: a cross-sectional study in Selangor, Malaysia - Ching, Siew-Mooi; Thurasamy, Ramayah; Cheong, Ai Theng; Yee, Anne; Lim, Poh Ying; Ismail, Irmi Zarina; Ng, Jun Ying; Ooi, Pei Boon; Lee, Kai Wei; Rasina Nilofer, Jabarulla Khan; Zamzurina, Asmuee; Rajini Ann, S. Ratnasingamp; et al. (Universiti Putra Malaysia, 2023)
Introduction: The aim of this study was to investigate how the COVID-19 pandemic has affected the mental health of primary healthcare providers in Malaysia, focusing specifically on the role of depression, anxiety, and stress in mediating the relationship between fear of COVID-19 and burnout. Methods: A web-based cross-sectional study was conducted with 1280 healthcare providers from 30 government primary care clinics. Participants completed several scales, including the COVID-19 Fear Scale, Copenhagen Burn Inventory Scale, and DASS-21 Scale, and mediation analysis was performed using Smart-PLS. Results: The majority of respondents were female (82.4%) and Malays (82.3%), with a mean age of 36 years and an average working experience of 11 years. Nurses (47.4%) were the largest group, followed by doctors (26%), medical assistants (11.9%), healthcare assistants (7.1%), medical laboratory technicians (6.4%), and drivers (1.3%). The findings revealed that fear of COVID-19 was positively associated with psychological distress, such as depression, anxiety, and stress, as well as burnout. Additionally, psychological distress played a mediating role in the relationship between fear of COVID-19 and three domains of burnout: personal burnout (β=0.154, p<0.001), work-related burnout (β=0.187, p<0.001), and client-related burnout (β=0.175, p<0.001). Conclusion: These results highlight the need for interventions to address the adverse effects of the COVID-19 pandemic on the mental health of healthcare providers, particularly in reducing depression, anxiety, and stress, which were found to play a positive mediating role in the development of burnout.